The Impact of Eloquence Arts on the Presentation of the Character in the Nūniyya Poem of Ibn Al-Haddad Al-Andalusi - M, BASMA (Journal of College of Education, 2020)
The poet Ibn Al-Haddad, died in 480 AH, has  a Nūniyya poem, whose figurative language has a special trait worthy of research attention. Ibn Al-Haddad  successfully used many artistic and semantic devices to achieve some aesthetic and semantic goals. Among the poetic figures he has employed are diversification, the anagrams /alliteration, the unnecessary necessity,  inclusion, and the style of wishful thinking and interrogation and other artistic devices. Many characters have met in this Nūniyya poem, including the character of the poet, Nuwaira Al-Habiba, Al-Mu'tasim Bin Samaadah, international philosophical characters, and the characters of  kings, as well as the character of Al-Banna who built Al-Mu'tasim’s Palace, and Sinmar who built Al-Khornaq’s Palace. Ibn Al-Haddad  was so keen in dealing with the character by using rhetorical art, which he saw as appropriate to present it, as we find these arts in certain characters, and are virtually nonexistent in other characters.
Keywords: Impact of Eloquence the Nūniyya Poem; Character